Partitioning and diffusion of PBDEs through an HDPE geomembrane. (September 2016) - Rowe, R. Kerry; Saheli, Pooneh T.; Rutter, Allison
Highlights: Gives first parameters for modelling PBDE diffusion through geomembranes in landfills. Shows that the geomembrane can be extremely effective as a diffusion barrier to PBDE. Holes in a wrinkle could cause unacceptable impacts on an underlying aquifer. Identifies need to pay more attention to potential PBDE migration from landfills. Abstract: Polybrominated diphenyl ether (PBDE) has been measured in MSW landfill leachate and its migration through a modern landfill liner has not been investigated previously. To assure environmental protection, it is important to evaluate the efficacy of landfill liners for controlling the release of PBDE to the environment to a negligible level. The partitioning and diffusion of a commercial mixture of PBDEs (DE-71: predominantly containing six congeners) with respect to a high-density polyethylene (HDPE) geomembrane is examined. The results show that the partitioning coefficients of the six congeners in this mixture range from 700, 000 to 7, 500, 000 and the diffusion coefficients range from 1.3 to 6.0 × 10 −15 m 2 /s depending on the congener. This combination of very high partitioning coefficients and very low diffusion coefficients suggest that a well constructed HDPE geomembrane liner will be an extremely effective barrier for PBDEs with respect to diffusion from a municipal solid waste landfill, as illustrated by an example. The results for pure diffusion scenario showed that the congeners investigated meet the guidelines by at least a factor of three for an effective geomembrane liner where diffusion is the controlling transport mechanism.